Analisis Data Penelitian - Lenni Masnidar Nasution (Hikmah, 2018)
Data analysis is the process of organizing and sorting data into patterns, categories and basic description units so that themes can be found and work hypotheses can be formulated as based on data. Research data collection techniques include: interviews, questionnaires or questionnaires, observation and documentation. Correlation Analysis is a study that discusses the degree of closeness of the relationship between variables, which is expressed by the Correlation Coefficient. Regression analysis is a study of the dependence of one or more X (independent variables) on Y (dependent variable), with the intention to predict the value of Y. The term hypothesis comes from Greek, that is from the word hupodan thesis. Hupo means temporary, or lacks the truth or the truth is still weak. While thesis means statement or theory.